The coupling of experiments with density functional theory in the studies of the electrochemical hydrogen evolution reaction. Issue 18 (27th April 2020) - Chen, Mingpeng; Smart, Tyler J.; Wang, Shanwen; Kou, Tianyi; Lin, Dun; Ping, Yuan; Li, Yat
Abstract : This article discusses the power of coupling experiments with DFT in obtaining insights into the fundamentals of HER, Qincluding explaining experimental results and revealing reaction mechanisms and facilitating the development of new HER electrocatalysts. Abstract : The hydrogen evolution reaction (HER) is the cathodic reaction of water electrolysis, which is a cleaner and more sustainable approach to produce hydrogen gas compared to the conventional steam reforming method. Electrocatalysts are essential to lower the overpotential of the HER and, thus, the overall energy cost of water electrolysis. The search for high performance HER catalysts has been facilitated by coupling experiments with first principles calculation, e.g., density functional theory (DFT). This article will first review the factors determining the performance of HER electrocatalysts. Then, we will discuss the power of coupling experiments with DFT in obtaining insights into the fundamentals of the HER, including explaining experimental results and revealing reaction mechanisms, and facilitating the development of new HER electrocatalysts. The last section of this review focuses on the limitations and progress of coupling experiments with DFT from three perspectives: experimental measurements, characterization and DFT simulation. Finally, we share some opinions about how to better couple experiments with DFT.